2022
DOI: 10.1063/5.0095126
|View full text |Cite
|
Sign up to set email alerts
|

SOI-based micro-mechanical terahertz detector operating at room-temperature and atmospheric pressure

Abstract: We present a micro-mechanical terahertz (THz) detector fabricated on a silicon on insulator substrate and operating at room-temperature. The device is based on a U-shaped cantilever of micrometric size, on top of which two aluminum half-wave dipole antennas are deposited. This produces an absorption extending over the [Formula: see text] THz frequency range. Due to the different thermal expansion coefficients of silicon and aluminum, the absorbed radiation induces a deformation of the cantilever, which is read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Moreover, they also mentioned that a room-temperature NETD below 10 mK appears feasible with further scaling and optimization. To date and to our knowledge, only one work [77] has demonstrated a MEMS resonator based on bending mode for THz detection, in addition to the previously reported GaAs double-clamped MEMS beam bolometer [59]. In that work, as schematically shown To date and to our knowledge, only one work [77] has demonstrated a MEMS resonator based on bending mode for THz detection, in addition to the previously reported GaAs double-clamped MEMS beam bolometer [59].…”
Section: Thz/ir Detection Based On Mems/nems Resonatorsmentioning
confidence: 91%
See 2 more Smart Citations
“…Moreover, they also mentioned that a room-temperature NETD below 10 mK appears feasible with further scaling and optimization. To date and to our knowledge, only one work [77] has demonstrated a MEMS resonator based on bending mode for THz detection, in addition to the previously reported GaAs double-clamped MEMS beam bolometer [59]. In that work, as schematically shown To date and to our knowledge, only one work [77] has demonstrated a MEMS resonator based on bending mode for THz detection, in addition to the previously reported GaAs double-clamped MEMS beam bolometer [59].…”
Section: Thz/ir Detection Based On Mems/nems Resonatorsmentioning
confidence: 91%
“…A number of groups have demonstrated that MEMS/NEMS resonators can work as fast and highly sensitive THz/IR detectors. Depending on the vibrational mode and geometrical shape, they can be categorized as torsional mode [72][73][74][75][76], bending mode [59,77], or membranous shape [57,78,79]. Table 1 provides a survey of the performance of THz/IR detectors based on MEMS/NEMS resonators, allowing for an objective comparison of existing MEMS bolometers.…”
Section: Thz/ir Detection Based On Mems/nems Resonatorsmentioning
confidence: 99%
See 1 more Smart Citation